Effect of Human Resource Management Practices on Employee Performance in Public Sector Organizations: A Systematic Review Utilising the UTAUT Framework - Phiri, Cassidy; Daka , Harrison; Phiri, Jackson (Proceedings of International Conference for ICT (ICICT) - Zambia, 2025)
This systematic review investigates the relationship between Human Resource Management (HRM) practices and employee performance within public sector organizations, framed by the Unified Theory of Acceptance and Use of Technology (UTAUT). The primary aim is to understand how specific HRM practices influence employee performance and explore the mediating role of technology adoption and acceptance in this context. A comprehensive literature search was conducted using multiple academic databases, applying targeted keywords related to HRM practices, employee performance, public sector organizations, and UTAUT. The collected studies were systematically analysed to extract relevant findings and insights. The review reveals that effective HRM practices significantly enhance employee performance in public sector organizations. It underscores the critical role of user-friendly technology, as emphasized by UTAUT, in facilitating HRM processes and fostering employee engagement. This study emphasizes the importance of aligning HRM strategies with technological advancements to optimize employee outcomes. However, limitations concerning the exclusion of grey literature and the generalizability of findings to the private sector are acknowledged. Future research is encouraged to further explore these relationships across diverse organizational contexts.